Direct effects of ethanol on neuronal differentiation: An in vitro analysis of viability and morphology - Guadagnoli, Tamara (2016)
The deleterious effects of ethanol (EtOH) on the brain have been widely described, but its effects on theneuronal cytoskeleton during differentiation have not yet been firmly established. In this context, ouraim was to investigate the direct effect of EtOH on cortical neurons during the period of differentiation.Primary cultures of cortical neurons obtained from 1-day-old rats were exposed to EtOH after 7 daysof culture, and viability and morphology were analyzed at structural and ultrastructural levels after24-h EtOH exposure. EtOH caused a significant reduction of 73±7% in the viability of cultured corticalneurons, by preferentially inducing apoptotic cellular death. This effect was accompanied by an increasein caspase 3 and 9 expression. Furthermore, EtOH induced a reduction in total dendrite length and in thenumber of dendrites per cell. Ultrastructural studies showed that EtOH increased the number of lipidicvacuoles, lysosomes and multilamellar vesicles and induced a dilated endoplasmatic reticulum lumenand a disorganized Golgi apparatus with a ring-shape appearance. Microtubules showed a disorganizeddistribution. Apposition between pre- and postsynaptic membranes without a defined synaptic cleft anda delay in presynaptic vesicle organization were also observed. Synaptophysin and PSD95 expression,proteins pre- and postsynaptically located, were reduced in EtOH-exposed cultures. Overall, our studyshows that EtOH induces neuronal apoptosis and changes in the cytoskeleton and membrane proteinsrelated with the establishment of mature synapses. These direct effects of EtOH on neurons may partiallyexplain its effects on brain development.